CALCULATING OF THE NUMBER OF APPLICATIONS ABSENT STMIK JAKARTA STI&K ATA 2007/2008 SEMESTER USING MICROSOFT VISUAL FOXPRO 9.0 - Armita Tri Utami; Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2010)
STMIK JAKARTA STI&K is a High School which is engaged in computer education, in everyday activities is made up of teaching and learning process called lectures. In lectures students must complete the activity absences with their respective initials. From the result of absenteeism, we can see the total number of incoming and incoming students. With the making of an application program design calculation of the number of absent students, it is expected to be useful for the interests of the absentee students and can be used properly. This application is built using Microsoft Visual FoxPro 9.0, because by using Microsoft Visual FoxPro 9.0 application program calculate the number of absences is to be easily designed by utilizing the various facilities provided by Microsoft Visual FoxPro 9.0, so this application easy to use and made with easy to view (the user friendly).